Answer:Your left hand side evaluates to:
m+(−1)mn+(−1)m+(−1)mnp
and your right hand side evaluates to:
m+(−1)mn+(−1)m+np
After eliminating the common terms:
m+(−1)mn from both sides, we are left with showing:
(−1)m+(−1)mnp=(−1)m+np
If p=0, both sides are clearly equal, so assume p≠0, and we can (by cancellation) simply prove:
(−1)(−1)mn=(−1)n.
It should be clear that if m is even, we have equality (both sides are (−1)n), so we are down to the case where m is odd. In this case:
(−1)(−1)mn=(−1)−n=1(−1)n
Multiplying both sides by (−1)n then yields:
1=(−1)2n=[(−1)n]2 which is always true, no matter what n is
Answer:
5, 9,13,17
Step-by-step explanation:
5 +4 +4+4
Consider this option (this is not the only way):
1. according to the condition 2345N is divisible by <em>6</em>, it means, that N is even number (0;2;4;6 or 8).
2. <em>6</em>=3*2, then the number 2345N is divisible by 3 also. It means, that the number (2+3+4+5+N)=(14+N) is divisible by 3, where N={0|2|4|6|8}.
3. using items 1 and 2:
(14+4)=18; only 18 is divided by 3, it means that N=4.
answer: 4.
Note also, that only 23451; 23454 and 23457 are divided by 3. Only 2345<u>4</u> is divided by 6 (2345<u>4</u>/6=3909).
Yes because 3² + 4² = 5²
to be sure
9 + 16 = 25
25 = 25
The correct answer is A. y = 2x +1
Explanation:
An equation is a statement that shows equality. In this context, the equation should lead to two equal numbers even if the values of y and x change. In this context, the correct equation is y= 2X + 1 because this is the only one, in which, the value of Y is always equivalent to 2x + 1. To prove this, let's replace y and x for the values of the table.
First column
5 = 2 · 2 + 1
5 = 4 + 1
5 = 5
Second Column
9 = 2 · 4 + 1
9 = 8 + 1
9 = 9
Third column
13 = 6 · 2 + 1
13 = 12 + 1
13 = 13
Fourth column
17 = 8 · 2 + 1
17 = 16 + 1
17 = 17